2022
DOI: 10.3390/cancers14164029
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent NOMO1 Gene Deletion Is a Potential Clinical Marker in Early-Onset Colorectal Cancer and Is Involved in the Regulation of Cell Migration

Abstract: The incidence of early-onset colorectal cancer (EOCRC; age younger than 50 years) has been progressively increasing over the last decades globally, with causes unexplained. A distinct molecular feature of EOCRC is that compared with cases of late-onset colorectal cancer, in EOCRC cases, there is a higher incidence of Nodal Modulator 1 (NOMO1) somatic deletions. However, the mechanisms of NOMO1 in early-onset colorectal carcinogenesis are currently unknown. In this study, we show that in 30% of EOCRCs with hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…10 In terms of genomic variant, the deletion of the NOMO1 gene has been reported as a clinical marker in EOCRC, and the regulation of cell migration has been suggested for its role in tumorigenesis. 42 In summary, our study showed concordance with those EOCRC studies that have reported EMT-related features of the biomarker in EOCRC, regarding that the EMT pathway was significantly distinct between EOCRC and LOCRC in our research. In another respect, some studies have identified immune-related gene expressions as a biomarker of EOCRC, suggesting that EOCRC was distinct in immunity compared to LOCRC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…10 In terms of genomic variant, the deletion of the NOMO1 gene has been reported as a clinical marker in EOCRC, and the regulation of cell migration has been suggested for its role in tumorigenesis. 42 In summary, our study showed concordance with those EOCRC studies that have reported EMT-related features of the biomarker in EOCRC, regarding that the EMT pathway was significantly distinct between EOCRC and LOCRC in our research. In another respect, some studies have identified immune-related gene expressions as a biomarker of EOCRC, suggesting that EOCRC was distinct in immunity compared to LOCRC.…”
Section: Discussionsupporting
confidence: 91%
“…Another recent study has reported that the biomarker of EOCRC, PEG10, that they identified played a role in tumor cell invasion 10 . In terms of genomic variant, the deletion of the NOMO1 gene has been reported as a clinical marker in EOCRC, and the regulation of cell migration has been suggested for its role in tumorigenesis 42 . In summary, our study showed concordance with those EOCRC studies that have reported EMT‐related features of the biomarker in EOCRC, regarding that the EMT pathway was significantly distinct between EOCRC and LOCRC in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have linked EOCRC to mutations in genes resulting in DNA‐repair deficiencies, histone modification, and increased cell turnover (Table 1). 25–28 This higher tumor mutational burden is important as it indicates the potential role and favorable response of EOCRCs to immune checkpoint inhibitors 29 . Knowledge of molecular characterization has not yet translated into therapeutic improvements.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have linked EOCRC to mutations in genes resulting in DNA-repair deficiencies, histone modification, and increased cell turnover (Table 1). [25][26][27][28] This is significant as a dysregulated innate immune response has been found to be the main driver behind "inflammaging", a phenomenon characterized by persistent low levels of systemic and tissue microenvironment inflammation. 32 Other studies investigating the relationship between certain environmental exposures and EOCRCrelated gene and metabolomic modifications have established links between inflammation, obesity, and the NOTCH1-GATA4-IRG1 axis, alcohol consumption and overexpression of NOTUM/GDF11, and red meat consumption and choline/tryptophan/bile acid accumulation and upregulation of phosphatidylcholine and tryptophan biosynthesis genes in EOCRC patients.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Heterozygous loss of NOMO1 (start: 14946287, end: 14959012) was also detected in index case 1. Colorectal cancer frequently exhibits NOMO1 deletion [ 60 , 61 ]. This biomarker is a potential therapeutic target for early-onset colorectal cancer [ 60 ].…”
Section: Discussionmentioning
confidence: 99%